Pembuktian Unsur Kerugian Perekonomian Negara pada Tindak Pidana Korupsi Sektor Sumber Daya Alam di Indonesia - Azrina, Nikmatul; Hafrida; Erwin (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to analyze the proof of the element of state economic loss in corruption crimes within the natural resources sector in Indonesia. The main issue lies in the distinction between state financial loss, which is concrete and measurable, and state economic loss, which is broad and abstract, thereby creating challenges in evidentiary processes. This research employs a normative juridical method using statutory and conceptual approaches. The results indicate that proving state economic loss requires a multidisciplinary approach, including the use of scientific evidence and economic analysis, as it cannot always be quantified with certainty like state financial loss. Furthermore, the absence of standardized methods for determining and calculating state economic loss leads to differing interpretations among law enforcement authorities. Therefore, criminal law reform is necessary to clarify the concept, evidentiary methods, and competent institutions in assessing state losses, in order to ensure legal certainty and effective law enforcement in corruption cases.